Determinants of Intangible Investment and Its Impacts on Firms’ Productivity: Evidence from Chinese Private Manufacturing Firms - Zhou, Yixiao; Yang, S.; Song, L. (Wiley-Blackwell, 2018)
Using data from the 2012 China Enterprise Survey conducted by the World Bank, this study examines the determinants of intangible investment by private manufacturing firms and its impacts on firms' productivity in China, thus shedding light on the recent development of intangibles in one of the largest emerging economies in the world. Higher human capital, larger firm size and better institutional quality are found to increase the propensity and the amount of intangible investment, yet fiercer market competition generally decreases both the propensity and the amount invested in intangibles. We provide evidence that the disaggregated components of intangibles are positively correlated with firm productivity and there is complementarity between software and organization investment. Implications for policies to enhance investment in intangibles are identified from the empirical results.